Conocimiento del proceso de atención de enfermería en estudiantes universitarios - Alvarez Cañares, Mairoby Jamileth; Riofrío Chávez, Aracelis Yesenia; Sotomayor Preciado, Anita Maggie; Zhunio Bermeo, Fanny Isabel (My University, 2021)
Introduction:The Nursing Care Process (PAE) is a scientific, systematic, and organized method used by nursingprofessionals to identify the problems and needs of the individual, family, and community. And at the same time provideefficient, humanistic individualized care; focused on achieving results.Objective:To evaluate the level of knowledge ofthe nursing care process in fifth-semester nursing students at the Technical University of Machala-Ecuador.Methodology:The present study has a quantitative, descriptive, and cross- sectional approach. The sample consisted of 58 studentswho are in the fifth semester of nursing at the Technical University of Machala, to whom a 17- question survey wasapplied, previously validated at the discretion of experts, to evaluate their knowledge about the PAE. The data analysiswas carried out using tables of frequencies and percentages through the statistical program SPSS 15.Results:In thestudied population, the female sex predominated with 77.6%. It was evidenced that 81.03% know the concept of thePAE, 65.52% recognize its importance and 90% correctly identify the stages of the nursing care process, however, there isconfusion regarding the primary source of collection of data in the assessment stage 51.72%.Conclusions:It is concludedthat the fifth-semester students of the nursing career have a medium level of knowledge about the definition, importance,stages, and application of the PAE, however, it is considered that This knowledge should be reinforced since significantdeficiencies were identified in terms of the correct processes in each of the stages of the PAE.
Introducción:El Proceso de atención de enfermería (PAE) es un método científico, sistemático y organizado, usado porlos profesionales de enfermería, para identificar los problemas y necesidades del individuo, familia y comunidad. Y a suvez brindar cuidados individualizados eficientes, humanistas; centrados en el logro de resultados.Objetivo:Evaluar elnivel de conocimiento del proceso de atención de enfermería en los estudiantes de quinto semestre de enfermería de laUniversidad Técnica de Machala-Ecuador.Metodología:El presente estudio tiene un enfoque cuantitativo, descriptivo yde tipo transversal. La muestra estuvo constituida por 58 estudiantes de quinto semestre de enfermería en la UniversidadTécnica de Machala, a quienes se les aplicó una encuesta de 17 preguntas, previamente validada a criterio de expertos, paraevaluar sus conocimientos acerca del PAE. El análisis de los datos se realizó mediante tablas de frecuencias y porcentajesa través del programa estadístico SPSS 15.Resultados:En la población estudiada predominó el sexo femenino conun 77,6 %. Se evidenció que el 81,03 % conoce el concepto del PAE, un 65,52 % reconoce su importancia y el 90 %identifica correctamente las etapas del Proceso de atención de enfermería, sin embargo, existe confusión en cuanto ala fuente primaria de recolección de datos en la etapa de valoración con un 51,72 %.Conclusiones:Se concluye que losestudiantes de quinto semestre de la carrera de enfermería, poseen un nivel medio de conocimientos acerca de la definición,importancia, etapas y aplicación del PAE, sin embargo, se considera que estos conocimientos deben ser reforzados, debidoa que se identificaron deficiencias significativas en cuanto a los procesos correctos en cada una de las etapas del PAE.
Keywords: ENFERMERIA; CONOCIMIENTO; PROESO DE ENFERMERIA; ESTUDIANTES